2016
DOI: 10.3171/2015.2.spine14973
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes and adverse events of minimally invasive versus open posterior lumbar fusion: meta-analysis and systematic review

Abstract: OBJECT The objective of this study was to determine the clinical comparative effectiveness and adverse event rates of posterior minimally invasive surgery (MIS) compared with open transforaminal or posterior lumbar interbody fusion (TLIF/PLIF). METHODS A systematic review of the Medline, EMBASE, PubMed, Web of Science, and Cochrane databases was performed. A hand search of reference lists was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
128
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(140 citation statements)
references
References 61 publications
5
128
2
2
Order By: Relevance
“…However, prospective randomized studies comparing the outcomes of standard versus minimally invasive TLIF are scarce [4]. Moreover, meta-analyses of the available literature have yielded conflicting conclusions [5, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…However, prospective randomized studies comparing the outcomes of standard versus minimally invasive TLIF are scarce [4]. Moreover, meta-analyses of the available literature have yielded conflicting conclusions [5, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…Khan et al 12 performed a meta-analysis of 30 studies and found minimally invasive TLIF to result in statistically significantly less blood loss, shorter lengths of stay, and fewer complications than open TLIF. Goldstein et al 9 similarly analyzed 26 studies and found that patients who underwent minimally invasive surgery were less likely than those who underwent open surgery to experience medical adverse events (risk ratio 0.39, 95% confidence interval 0.23-0.69, p = 0.001) but not surgical adverse events. Medical adverse events included UTI, respiratory complications, cardiac complications, and need for transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the short term, compared to conventional open approaches, MIS techniques can reduce blood loss, operative times, postoperative pain, narcotic use, length of stay, postoperative surgical site infections, and medical resource use and time to adjuvant treatments. [61425262930] These characteristics are particularly salient in oncology patients, for whom surgery is targeted at pain relief and preservation of function rather than cure during their limited life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…The desire to reduce surgical morbidity further has stimulated interest in accomplishing the same goals through minimally invasive surgery (MIS). The evolution of MIS techniques in general permits satisfactory neural decompression and spinal stabilization across the gamut of spinal pathology, while offering reductions in blood loss, length of stay, recovery time, and complications[6789]—all highly desirable features when treating patients with potentially limited life expectancies.…”
Section: Introductionmentioning
confidence: 99%